Further studies into the reactivity and coordination chemistry of [Ge-9](4-) Zintl ions. The indium-containing anions [In(Ge-9)(2)](5-), [(Ge-9)(2)In(C6H5)](4-) and [Ge-9{In(C6H5)(3)}(2)](4-) - Hansen, D; Zhou, B; Goicoechea, J (2012)
Reactions between ethylenediamine solutions of K4Ge9 and triphenylindium yielded three novel Zintl ions, [In(Ge9) 2]5- (1), [(Ge9)2In(C 6H5)]4- (2), and [Ge9{In(C 6H5)3}2}]4- (3). Species 1 exhibits an indium metal atom coordinated by two nine-atom germanium cages which bond to the central metal in an η3-mode. The "staggered" arrangement of the two clusters confers the indium metal centre an octahedral coordination geometry. Species 2 displays trigonal planar coordination around the indium atom with an [In(C6H 5)]2+ moiety acting as a bridge between the two halves of a [Ge9-Ge9]6- dimer. Finally, species 3 is composed of a [Ge9]4- deltahedral Zintl ion acting as a Lewis base to two In(C6H5)3 moieties. All three anions were characterized in the solid-state by single-crystal X-ray diffraction in [K(2,2,2-crypt)]5[1]·2en, [K(2,2,2-crypt)] 4[2]·3tol and [K(2,2,2-crypt)]4[3], respectively. The existence of the anions in solution was confirmed by electrospray mass-spectrometry. DFT level calculations were also conducted on all of the cluster anions. ©2012 Elsevier B.V. All rights reserved.